High thermoelectric performance of graphite nanofibers. Issue 8 (7th February 2018) - Tran, Van-Truong; Saint-Martin, Jérôme; Dollfus, Philippe; Volz, Sebastian
Abstract : This work unveils the outstanding thermoelectric properties of graphite nanofibers. Abstract : Graphite nanofibers (GNFs) have been demonstrated to be a promising material for hydrogen storage and heat management in electronic devices. Here, by means of first-principles and transport simulations, we show that GNFs can also be an excellent material for thermoelectric applications thanks to the interlayer weak van der Waals interaction that induces low thermal conductance and a step-like shape in the electronic transmission with mini-gaps, which are necessary ingredients to achieve high thermoelectric performance. This study unveils that the platelet form of GNFs in which graphite layers are perpendicular to the fiber axis can exhibit outstanding thermoelectric properties with a figure of merit ZT reaching 3.55 in a 0.5 nm diameter fiber and 1.1 in a 1.1 nm diameter one. Interestingly, by introducing 14 C isotope doping, ZT can even be enhanced up to more than 5, and more than 8 if we include the effect of finite phonon mean free path, which demonstrates the amazing thermoelectric potential of GNFs.